The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/ptr.7444
|View full text |Cite
|
Sign up to set email alerts
|

Dietary polyphenols for management of rheumatoid arthritis: Pharmacotherapy and novel delivery systems

Abstract: Rheumatoid arthritis (RA) is a chronic, complex, systemic autoimmune disease causing chronic inflammation, swelling, and pain. It affects pulmonary and ocular physiology, gastrointestinal disturbance, skeletal disorders, and renal malfunctioning. Although conventional and biological drugs available to treat RA are potent and effective, they lead to life‐threatening side effects and patient discomfort. Hence, alternative therapies are explored for their treatment which is safe, effective, and economical. Herbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…Rheumatoid arthritis (RA), one of the common types of chronic and pharmacologically complex systemic autoimmune disease observed in the elderly population, 242 , 268 , 269 , 270 is characterized by the presence of AAbs such as rheumatoid factor (RF) and anti‐cyclic citrullinated peptide antibody. 271 , 272 Liu et al.…”
Section: Treg Subsets In Autoimmune Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA), one of the common types of chronic and pharmacologically complex systemic autoimmune disease observed in the elderly population, 242 , 268 , 269 , 270 is characterized by the presence of AAbs such as rheumatoid factor (RF) and anti‐cyclic citrullinated peptide antibody. 271 , 272 Liu et al.…”
Section: Treg Subsets In Autoimmune Diseasementioning
confidence: 99%
“…Rheumatoid arthritis (RA), one of the common types of chronic and pharmacologically complex systemic autoimmune disease observed in the elderly population, 242,[268][269][270] is characterized by the presence of AAbs such as rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibody. 271,272 Liu et al have found that the frequency of circulating CD4 + CXCR5 + FOXP3 + Tfrs (Figure 3) and the ratio of Tfrs/Tfhs were significantly increased in patients with stable RA than in patients with active RA or healthy people.…”
Section: Treg Subsets In Rheumatoid Arthritismentioning
confidence: 99%
“…The BCL2 family of proteins is the hallmark of apoptosis regulation. 48 New members of the BCL2 gene family were discovered and cloned and were found to be differentially expressed in many types of cancer. BCL2 protein family, through its role in the regulation of apoptotic pathways, is possibly related to cancer pathophysiology and resistance to conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that also many naturally occurring compounds may be promising therapeutic options for the improvement of CVD risk. Antioxidant and anti-inflammatory effects of flavonoid and non-flavonoid polyphenols are well-documented [ 535 ]. Mainly in patients with chronic inflammatory conditions, polyphenols could improve HDL function, enhance RCT or protect HDL particles against dysfunction.…”
Section: Currently Available Hdl-targeted Therapiesmentioning
confidence: 99%